Volume 1: Symposia, Parts a and B 2012
DOI: 10.1115/fedsm2012-72307
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Breakup of Elliptical Liquid Jet in Still Air

Abstract: Numerical simulation of liquid jets ejecting from a set of elliptical jets with different aspect ratios between 1 (circular) to 3.85 is performed for several Weber numbers ranging 15 to 330. The axis-switching phenomenon and breakup length of the jets are characterized by means of a Volume of Fluid (VOF) method together with a dynamic mesh refinement model. This three dimensional simulation is compared with a recent experimental work and the results agree well. It is concluded that at Weber numbers less than 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Researchers have used the VOF model to simulate the two-phase flow of nozzle, bearing, and gear [25][26][27][28][29] and the primary breakup of the liquid jet. 30,31 The VOF model was developed by Hirt and Nichols 32 in 1981, which can model two or more immiscible fluids by solving a single set of momentum equations. For the oil-gas two-phase flow inside the under-race lubrication system, a volume fraction α oil is solved to describe the oil phase in the VOF model.…”
Section: Two-phase Flow Modelmentioning
confidence: 99%
“…Researchers have used the VOF model to simulate the two-phase flow of nozzle, bearing, and gear [25][26][27][28][29] and the primary breakup of the liquid jet. 30,31 The VOF model was developed by Hirt and Nichols 32 in 1981, which can model two or more immiscible fluids by solving a single set of momentum equations. For the oil-gas two-phase flow inside the under-race lubrication system, a volume fraction α oil is solved to describe the oil phase in the VOF model.…”
Section: Two-phase Flow Modelmentioning
confidence: 99%
“…To better track the trends, the results were divided into two sets. The results of LD(3), LD (6) and LD(10) nozzles were separated from LD(20), LD(40) and LD(60) nozzles. In contrast to the wavelength, it was found that the entrance length directly influenced the amplitude.…”
Section: Axis-switching Characteristicsmentioning
confidence: 99%
“…The axis-switching phenomenon and jet breakup in low speeds were also investigated through numerical simulations conducted by Farvardin and Dolatabadi. 6 It was analytically found by Pillai et al 7 that axis-switching was not the only source of instability for elliptical jets and even in the absence of axis-switching, an elliptical jet was less stable than a circular jet, apparently owing to its interfacial curvature effects. Recently, the axis-switching amplitude of free-falling elliptical jets was further examined by Ma and Zhu.…”
Section: Introductionmentioning
confidence: 98%
“…One may note that the jets' transitioned liquid core for both cases show surface features pertaining to low Re turbulent behavior. In order to fully characterize such perturbations and to resolve the surface waves in jets due to turbulence, previous studies by Farvardin and Dolatabadi (2013) have pointed out that a full 3D model using Large Eddy Simulations (LES) together with VOF method would be more ideal. We also envisage that the choice of LES-VOF should resolve such higher order surface effects and further enhance the agreement between predicted average jet lengths with experimentally determined results from Sallam et.…”
Section: Jetting: Varying Jet Breakup Length and Coalescence Of Dropsmentioning
confidence: 99%